Strategi Iklan pada Kampanye Partai Amanat Nasional (PAN) di Pemilu 2024 - Mauludin, Iman; Melia Jamila Oktasyania Bahreis2; Tasya Ashma Rianda; Rafli Januardi; Pangesti, Azwa Rozaf; Pia Khoirotun Nisa (Lembaga Intelektual Muda (LIM) Maluku, 2024)
All political parties and their cadres must have a precise strategy to win as many votes as possible. The National Mandate Party (PAN) is no exception, they have a quite interesting strategy by utilizing electronic media and social media. The purpose of this study is to identify and explain whether the strategy used by the PAN party in its advertising strategy is successful or not in the 2024 election. Hypodermic Needle Theory or syringe theory is the main foundation for understanding advertising strategies and their impact in the political arena. This writing method takes the literature study method, namely the research stage by collecting literature sources, both primary and secondary. The main source of data for this study is the research article published through google scholar. The results of the research show that the PAN Party has succeeded in carrying out its strategy, making political advertisements by carrying concepts relevant to the current era and utilizing technology and the internet by publishing it through social media platforms.